The effect of pair work to student’s ability on writing recount text for junior high school students - Tamami, Aulia Ihktiar; Styati, Erlik Widiyani; Kurniawan, Arri (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
The research aim at investigating the effect of pair work to students ability in writing recount for junior high school students. The quasi-experimental research used in this study. The participants were the students of MTsN Kota Madiun. The researchers used writing test to collect the data. In analyzing the data, the researchers use independent t-test. The result shows that there is a significant difference in writing skills of students taught using pair work and conventional teaching between the experimental class and the control class. Students who are taught using pair work gain higher scored than students who are taught using conventional teaching. The results obtained that the significance value of equal variances is assumed to be 0.001, it could be concluded that it is smaller than 0.05 (0.001 < 0.05). This means that pair work method brings many benefits for students to write their writing skills.